Learner Narratives of Translingual Identities A Multimodal Approach to Exploring Language Learning Histories - Kiernan, Patrick (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book addresses translingual identities through an innovative multimodal analysis of the language learning histories of a class of advanced learners of English in Japan who grew up between two or more languages. The author explores both the translingual experiences of those in the classroom and how they use language and gesture when describing their experiences to each other. This approach uses three perspectives: it looks at the worlds and identities the interviewees construct for themselves; at their interpersonal communication; and at the way they frame their experience. Finally, it offers some lessons based on the observations of the class which reveal the values they share and the key to their success as language learners. It will appeal to applied linguistic and educational researchers, particularly those with an interest in narrative approaches to exploring educational contexts, as well as language educators and policy makers interested in gaining a learner perspectiveon language learning. Patrick Kiernan is Associate Professor in the School of Business Administration at Meji University in Tokyo, Japan.